302 Metastatic: Benign Lymph Node Ratio (LNR) and Lymph Node Yield (LNY) as Predictors of Survival in Resected Colorectal Cancer (CRC). (28th February 2022) - Issa, M.; Ahmad, S.; Vijayagopal, K.A.; Freeborn, S.; Omolokun, O.; Griffine, A.; Wilson, J.; Magee, C.
Abstract: Background: Lymphadenectomy is central to tumor prognosis. 12 LNY during CRC resection is a standard of good oncological resection, but 30–50 percent of resections do not achieve this. LNR was suggested to be a more accurate predictive factor. Aim: To examine the prognostic significance of LNY and LNR on survival in patients with non-metastatic CRC. Method: A retrospective study on patients with CRC treated at a DGH from January 2015 to February 2017. Outcome measures were Disease-Free (DFS) and Overall Survival (OS). Results: 265 cases were identified. The mean age was (71.4±11.3) years with a median follow-up of 56 (range 0–72) months. Median LNY was 18 (range 0–66) nodes. 74.9% of the cases have> 12 LNY and only 25.1% of the cases have < 12 LN yielded in the specimen; however, 76.4% have LNR of 0-<0.25. Increasing LNR was associated with poorer OS and DFS (p-value 0.0001). An LNR of (0.75–1) was associated with a very poor prognosis (p-value 0.0001); it showed 30 and 33 months less in median OS and DFS retrospectively than LNR (0-<0.25). LNY did not show any statistically significant predictive factor in survival. Multivariate analysis showed OS and DFS are affected (R2 = 27.3% and 26.1% retrospectively) mainly by LNR. It did not show statistical significance with the other variables, including TNM, LNY, and Dukes' stages. Conclusions: Increasing LNR was a marker of poor survival; however, LNY was not a statistically significant predictive factor. LNR is better in predicting survival than TNM and Dukes' staging.